1992
DOI: 10.4028/www.scientific.net/msf.97-99.59
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Defect Cluster Distributions during Irradiation

Abstract: lh» lubmiMd ranuwtipi hat bm amhntd by a axuncuc al *• US. Gawmnsnl undar ccmnaNo. W-31-10e-tfN6-3H A/xcnXnfr. torn U.S. Gwwimnl Main* a nonodmiw. royalty-fit* Ifcarw to pubM or fapiodunth* pubtkhad torn a) Mi contfbutkw. or akmi amwioJoto. tor U.S. Gowmnnni pufpowt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Neither of these approaches takes into account that a significant fraction of the defects surviving the cascade event are in the form of small defect clusters which contribute to the sink strength. [26,27] In the following we will include the effects of defect clusters on the freely migrating defect population.…”
Section: Defect Productionmentioning
confidence: 99%
“…Neither of these approaches takes into account that a significant fraction of the defects surviving the cascade event are in the form of small defect clusters which contribute to the sink strength. [26,27] In the following we will include the effects of defect clusters on the freely migrating defect population.…”
Section: Defect Productionmentioning
confidence: 99%
“…Along similar lines, Naundorf et al [40,41] showed that single defect pairs created at a sufficient distance (larger than the spontaneous recombination radius) from any other defects in a cascade would account for the observed magnitude of freely migrating defect fraction. Neither of these approaches takes into account that a significant fraction of the defects surviving the cascade event are in the form of small defect clusters which not only remove defects from those available for long-range migration, but also contribute to the sink strength and, therefore, reduce the lifetime of defects released into the matrix [42,43]. It should be emphasized that the quantity important for microstructural evolution is the "free defect population", i.e., the product of the number of defects released into the matrix and the average number of jumps the defects undergo before annihilation, rather than the number of defects released per se.…”
Section: Displacement Cascade Characteristicsmentioning
confidence: 99%
“…Wiedersich [20] has suggested the following simple empirical expression to describe the fraction of freely-migrating defects, p(N), produced in cascades of various sizes:…”
Section: Il Defect Survival Vs Freely-migrating Defect Productionmentioning
confidence: 99%
“…More recently, Wiedersich [14,20] has examined the possible role of defect clusters in enhancing intercascade recombination, and therefore their role in reducing the number of freely-migrating defects. He argued that computer simulations indicate that only about one-half of the additional decrease arises from intracascade annealing at elevated temperatures, but that the larger observed decrease can be rationalized in terms of uncorrelated defect annihilation at previously produced clusters.…”
Section: T Vs Intercascade Defect Annihilation: the Role Of Cascade mentioning
confidence: 99%